Pemanfaatan Fly Ash Dan Bottom Ash (FABA) Sebagai Solusi Inovasi Pengolahan Limbah Dalam Mendukung Keberlangsungan UMKM Dalam Bidang Pembuatan Batako, Paving Blok Dan Pengecoran - Wahyu syawaliani; SetioUtomo (JURNAL BISNIS DAN PEMBANGUNAN, 2024)
Utilization of Fly Ash and Bottom Ash (FABA) as a Waste Management Innovation Solution in Supporting the Sustainability of Umkm in the Field of Brick Making, Paving Blocks and Casting. This research aims to understand the impact of Fly Ash and Bottom Ash implementation as a business innovation on Micro, Small, and Medium Enterprises (MSMEs) and its potential in supporting business sustainability and consumer purchasing power. This study used a qualitative approach, data were collected through interviews, observations, document searches, and literature studies. The results show that the utilization of FABA from Balikpapan Bay power plant has succeeded in creating a valuable innovation also supports consumer purchasing power through affordable selling prices and good quality, and provides sustainable growth opportunities